DIMENSIONAL STABILIZATION OF Celtis mildbraedii(ESA FUFUO) A TROPICAL HARDWOOD SPECIES - Marfo, E. D.; Wereko, E. Y. (UDS International Journal of Development, 2018)
Celtis mildbraedii (esa fufuo) is a high density hardwood; however esa fufuo has a medium dimensional stability. In this study, esa fufuo was chemically modified with acetic anhydride (AA) and propionic anhydride (PA) in dry pyridine to improve its dimensional stability. The dimensional stability of the modified samples was found to be superior to the unmodified samples. The average percentage volumetric swelling coefficient (%S) values of the modified and unmodified samples were AA = 5.09a, PA = 5.21b and De-ionized water= 7.28c.The average percentage water absorption coefficient (%WAC) values of the modified and unmodified samples according to the treatment were AA = 47.80a, PA = 48.01a, De-ionized water (DW) = 84.70b. The AA modified samples were better dimensionally stabilized when using %S followed by the PA modified samples and the DW samples which were the least stabilized. However, by using %WAC there was no significant difference in dimensional stabilization between AA and PA modified samples. The percentage anti-shrink efficiency (%ASE) of the AA modified samples was higher than that of the PA modified samples (AA = 29.26b, PA = 28.21a) indicating a superior dimensional stability for AA modified samples to that of PA. The water repellent efficiency (%WRE) of AA = 43.604a and PA = 43.458a, which indicated that there was no significant difference between the AA and PA modified samples. Â  Keywords: Dimensional Stability, Cellulose, Hemicelluloses, Lignin